Wages and Participation - Welch, Finis (Journal of Labor Economics, 1997)
During the last 25 years, annual hours worked by prime aged men fell by the equivalent of six 40-hour workweeks. The reduction was more pronounced among those younger than among mid-age workers, among black men than among white men, and among those with less schooling. Thus hours worked not only fell but showed increased dispersion, increases that paralleled the growth in wage dispersion that has become so familiar to students of trends in wages. The argument advanced here is that the correspondence is not coincidental; the changes in hours worked are simply the labor supply responses that follow the changes in the structure of wages.